Computations of the M-Polynomials and Degree-Based Topological Indices for Dendrimers and Polyomino Chains - Young Chel Kwun; Adeel Farooq; Waqas Nazeer; Zohaib Zahid; Saba Noreen; Shin Min Kang (International Journal of Analytical Chemistry)
Topological indices correlate certain physicochemical properties like boiling point, stability, and strain energy of chemical compounds. In this report, we compute M-polynomials for PAMAM dendrimers and polyomino chains. Moreover, by applying calculus, we compute nine important topological indices of under-study dendrimers and chains.